ANALISIS MARKET OVERREACTION DI BURSA EFEK INDONESIA PADA MASA 100 HARI KERJA JOKOWI-JK - Hiendarto, Ongky; Indrawati, Nur Khusniyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study examined the existence of the phenomenon of market overreaction in the Indonesia Stock Exchange during the 100 days of work Jokowi-JK. Furthermore, this study aims to determine whether the amount of change in the percentage of sectoral indices will be followed by a price reversal in the next period. Tests on the market overreaction done using one sample t-test two-way against abnormal return sectoral indices. Model abnormal return calculations used in this study is the market-adjusted model. Meanwhile, testing of the occurrence of price reversal is done by using multiple linear regression analysis. Multiple linear regression was done by regressing the dependent variable cumulative abnormal return to the independent variable abnormal return and market capitalization. The results show that of the 9 sectors in the Indonesian Stock Exchange, there are only two sectors that have abnormal return statistically significant, namely: property sector and infrastruc sector. Property sector has a positive abnormal returns, meaning that experienced a bullish trend during the study period. Meanwhile, infrastruc sector has a negative abnormal returns, meaning that experienced a bearish trend during the study period. Market overreaction that occurs in the property sector was not followed by a price reversal in the next period. Although not significant price reversal, but the variable coefficients abnormal return property sector has a negative value. These results give a signal that the bullish trend in the property sector has the potential to continue in the next period, but will experience a slight slowdown. Meanwhile, market overreaction that occurs in infrastruc sector followed by a price reversal in the next period. Price reversal happened a signal that the bearish trend in the sector infrastruc will potentially turn into a bullish trend in the next period. Keywords: market overreaction, price reversal, abnormal return.